(untitled) (Acta Polytechnica CTU Proceedings, 2022)
Adequacy of a structural fire design can in theory be demonstrated through a probabilistic risk assessment (PRA) where the compliance with tolerability limits and the ALARP requirement are explicitly ascertained. However, explicit assessment of ALARP requirement is challenging and impractical for day-to-day designs, due to the burden of estimating uncertain future costs and current safety investment costs. For normal design conditions, the use of target reliability indices has been recommended instead. These target reliability indices however have not been defined for structural design under fire events. To address this gap, the current study demonstrates a method to derive target reliability indices for a fire-exposed structure. As a case study, an insulated steel column (with varying levels of ISO fire rating) exposed to parametric natural fires is considered. The target reliability indices are derived for the steel column for varying fire exposure scenarios, considering different fire load densities and opening factor, relating to the building occupancies. This study thus investigates the important issue of adopting target reliability indices in fire design that are cost-optimized from quantitative analyses considering natural fire exposures, which has significant implications for fire safety and rational use of resources in the construction industry.